2010
DOI: 10.1080/13594320902995916
|View full text |Cite
|
Sign up to set email alerts
|

The use of artificial neural networks and multiple linear regression in modelling work–health relationships: Translating theory into analytical practice

Abstract: Although psychological theory acknowledges the existence of complex systems and the importance of nonlinear effects, linear statistical models have been traditionally used to examine relationships between environmental stimuli and outcomes. The way that we analyze these relationships does not seem to reflect the way that we conceptualize them. The present study investigated the application of connectionism (artificial neural networks) to modeling the relationships between work characteristics and employee heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Likewise, several studies have found that employee flourishing tends to behave in a nonlinear way Navarro, 2009, 2011;Guastello et al, 1999;Losada and Heaphy, 2004). Ergo, organizational researchers are increasingly favouring a nonlinear dynamical systems approach, which considers nonlinearity and discontinuous change, to study employee happiness and well-being (e.g., Navarro, 2009, 2011;Guastello, 2002;Karanika-Murray and Cox, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, several studies have found that employee flourishing tends to behave in a nonlinear way Navarro, 2009, 2011;Guastello et al, 1999;Losada and Heaphy, 2004). Ergo, organizational researchers are increasingly favouring a nonlinear dynamical systems approach, which considers nonlinearity and discontinuous change, to study employee happiness and well-being (e.g., Navarro, 2009, 2011;Guastello, 2002;Karanika-Murray and Cox, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…RI is an effect size metric that specifies the importance of a predictor considering all others, providing a description of the weights of all input variables (Lucek & Ott, 1997). A relative importance greater than .10 indicates major contributions, whereas those between .05 and .10 represent moderately, but still important, contributions (e.g., Karanika-Murray & Cox, 2010). As it is reported in Table 4, the high propensity for emotional contagion group was significantly (RI > .05) influenced by approximately all listed events, independently of their valence (nine out of thirteen events).…”
Section: Exploring the Moderating Role Of Employees' Propensity For Ementioning
confidence: 85%
“…For the analyses, the sample was randomly divided in two: 70% assigned for training and 30% allocated for testing. This procedure allows us to track the errors and to prevent over-training (e.g., Karanika-Murray & Cox, 2010). We used batch training because it reduces the total error and it is more accurate to small-medium datasets.…”
Section: Hypothesis Testing: Artificial Neural Networkmentioning
confidence: 99%
“…Importantly, the detection of nonlinearity and interactions using these techniques can happen without prespecification of the exact pattern of nonlinearity. Numerous studies have found that artificial neural networks often outperform traditional regression based techniques in terms of their ability to predict counterproductive work behaviors (Collins & Clark, 1993), employee health (Karanika-Murray & Cox, 2010), turnover (Somers, 1999), and job satisfaction and performance (Somers & Casal, 2009). In all of these instances, the superiority of the artificial neural network was attributed to its ability to accommodate nonlinearity, even when compared to regression approaches with nonlinear terms included.…”
Section: How Big Data Analytics Will Impact Our Methodsmentioning
confidence: 99%